Prototype of The Quran and Translation of The Ministry of Religion 2019 Edition in Quran Live Chat on Whatsapp and Telegram Applications - Tanoto, Fakhri Putra (Jurnal Penelitian Ilmu Ushuluddin, 2021)
This study aims to integrate the Qur'an and its translation in an instant messaging application. The method used This research uses a mixed method, which combines qualitative and quantitative methods. This study resulted in a product in the form of a chatbot named Quran Live Chat and concluded that there were benefits felt by users in searching for the latest verses and translations belonging to the Ministry of Religion for the 2019 edition of the refinement by using instant messaging applications such as Whatsapp and Telegram. This study recommends that further research be carried out related to the integration of the book of interpretation.